Akibat Hukum Terhadap Pembatalan Akta Perjanjian Pengikatan Jual Beli (PPJB) Tanah di Kota Makassar (Studi Kasus Kantor Notaris Kota Makassar) - Sumarna, M. Ibnu (Fakultas Hukum Universitas Muhammadiyah Palu, 2022)
The sale and purchase binding agreement may be canceled unilaterally by one party or upon the agreement of both parties, but the cancellation of an authentically made deed of agreement will certainly bring certain juridical consequences. This study aims to examine and analyze the legal consequences of the cancellation of the Land Purchase Agreement (PPJB) in Makassar and the factors that influence the cancellation of the land sale and purchase agreement deed in the city of Makassar. This type of research is Empirical Law research. The data used are primary data, namely data directly obtained from field research (interviews) and questionnaires (questionnaires) and secondary data obtained through scientific journals, scientific articles with the aim of completing primary data. Then it was analyzed qualitatively using the theory of legal certainty as an analyst knife and presented descriptively. The results of the study indicate that: The legal consequences of canceling the binding agreement on the sale and purchase of land are fines in the form of refunds by the seller to the buyer, because the seller does not fulfill his pre-determined obligations. Factors that affect the cancellation of the sale and purchase binding deed are the obligation to pay the seller's and buyer's taxes, and the mutually agreed sale and purchase price cannot be repaid until the agreed time period.